Switching “Real-World” Diabetes Patients to Degludec from Other Basal Insulins Provides Different Clinical Benefits According to Their Baseline Glycemic Control - Tentolouris, Nikolaos (Adv Ther, 2019)
INTRODUCTION: The stable, ultra-long duration of action of insulin degludec (degludec) minimizes fluctuations in glucose-lowering activity over the daily (24-h) dosing period, and comparative studies with other basal insulins suggest that these properties translate into a lower risk of hypoglycemia at equivalent levels of glycemic control. Results from the real-world European multicenter, retrospective chart review study of 2550 patients with type 1 and type 2 diabetes (T1D and T2D) in routine clinical care EU-TREAT (NCT02662114) showed that patients benefited from improved glycemic control and significantly reduced rates of hypoglycemia following a switch to degludec. METHODS: In this post hoc analysis, EU-TREAT patients were stratified into good (≤ 7.5% HbA1c), intermediate (> 7.5 to ≤ 8.5% HbA1c), and poor (> 8.5% HbA1c) glycemic control at baseline to investigate the possibility of differential benefits, either improved control or reduced risk of hypoglycemia, whichever the need. Changes in HbA1c, overall hypoglycemia, and total insulin dose from baseline to 6 and 12 months follow-up were assessed for each group. RESULTS: For both T1D and T2D patients, those in good initial control experienced significant reductions in rates of hypoglycemia and total insulin dose following the switch, without compromising control. Those in poor initial control achieved significant improvements in HbA1c with no change in rates of hypoglycemia or total insulin dose. CONCLUSION: This analysis expands the findings of EU-TREAT by showing differential changes in the clinical endpoints depending on particular need. It introduces the possibility that the differential benefits of degludec could address two of the renowned clinical challenges faced when treating diabetes: improving glycemic control for optimal management of T1D and titrating insulin dose in T2D, both without fear of increased hypoglycemia. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02662114. FUNDING: Novo Nordisk A/S. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12325-019-00916-7) contains supplementary material, which is available to authorized users.